ANALISIS KEBUTUHAN BUKU TEKS STRATEGI PEMBELAJARAN BERBASIS PENDIDIKAN KARAKTER - Amelia Ayuningsih; Agus Darmuki; Nur Alfin Hidayati (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to describe the analysis of the needs for textbooks for learning strategy courses in the Indonesian Language and Literature Education Study Program. The focus of this needs analysis is on the shortcomings and desires of students related to learning strategy textbooks. This research method uses a qualitative description. Data collection through a series of questionnaires was distributed to students of PBSI IKIP PGRI Bojonegoro to analyze the needs, shortcomings, and motivation to learn learning strategies for the needs of prospective teachers. This survey research uses a series of questionnaires that includes three steps to determine the needs of students and lecturers. The research subjects were level II students in the fourth semester of the PBSI IKIP PGRI Bojonegoro Study Program, which amounted to 32 people. Analysis of the data used quantitative analysis. Interviews used in the form of open interviews were conducted with lecturers and students. Observation instruments are also used to determine the learning process of learning strategy courses in the classroom. The results showed that the available learning strategy textbooks were still limited and the appearance of the books did not match the characteristics of students so that they felt less interested in reading. In addition, students also have difficulty understanding the text, because the language used is less communicative and there are some vocabulary that is difficult to understand and the text books available in the field have not integrated character education values. In conclusion, students and lecturers need a textbook of learning strategies based on character education values.